Entrepreneurial Self-Efficacy and Business Growth: Insights from Women Entrepreneurs in South Africa - Mahalia Lerato Molema (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Objective: Entrepreneurial self-efficacy (ESE), rooted in Bandura’s Social Cognitive Theory, refers to an individual’s belief in their ability to perform the tasks required to run a successful business. This study reviews and synthesises literature on the influence of ESE on business growth among women entrepreneurs in South Africa, focusing on four dimensions: entrepreneurial motivation, behavioural change, innovation, and performance outcomes. These interconnected elements are examined to understand how they shape ESE and contribute to sustainable business growth. The study also highlights the role of a supportive entrepreneurial ecosystem in fostering motivation, adaptability, innovation, and performance, enabling women to strengthen enterprises and advance inclusive economic development. Research Design & Methods: An integrative literature review was conducted to synthesise diverse study designs and theoretical perspectives. Searches included Scopus, Web of Science, EBSCOhost, JSTOR, and Google Scholar. Of 83 publications identified, 54 met inclusion criteria and were analysed in depth. Findings: High ESE enhances women entrepreneurs’ ability to manage complex tasks, adapt to challenges, pursue innovation, sustain motivation, and exercise behavioural control, supporting business growth. Implications & Recommendations: Entrepreneurial motivation builds confidence and persistence; an internal locus of control drives positive change; innovation enhances strategies; and improved performance boosts sales, reach, and efficiency. These insights guide policymakers, program designers, and ecosystem stakeholders in supporting women’s entrepreneurship. Contribution & Value Added: The study positions ESE as a driver of economic opportunities, job creation, and inclusive growth, providing evidence-based guidance for policymakers, program designers, and ecosystem stakeholders.